Variáveis ambientais predizem a estrutura da comunidade parasitária de Moenkhausia forestii em ambientes semi-lóticos em uma planície Neotropical. - Oda, Fabrício Hiroiuki (2014)
The biology and ecology of small fishes are poorly studied in Brazil. Aspects such as the small size and low commercial value are probably two factors that decrease the interest in studying these organisms. However, small size fishes have an important ecological role in the aquatic ecosystems, because they are food source for many animal groups. Natural events and human activities in aquatic environments such as construction of dams, alter the hydrological regime of water bodies, which affect the biological condition of the fish, influencing directly and indirectly the parasite community. By presenting an intimate relationship with their hosts and the surrounding environment, the parasites are excellent models for the study of different organizational patterns at different scales. Host characteristics, such as diet, body size, vagility, and reproductive behavior, which can be affected by variations in the characteristics of aquatic environments, also influence the structure of parasite communities. In addition, in the life cycle of the parasites, the small size fish can act as intermediaries and/or parathenic hosts because they serve as food for fish and other species of various groups of animals, which are considered definitive hosts. The upper Paraná River floodplain presents a wide variety of environments including lotic, lentic and semilotic water bodies, swamps, and other types of habitat completely covered by aquatic vegetation. This diversity of environments associated with the presence of macrophytes support high abundances of individuals and species of fish, including sedentary species of small size. Shoals of these species are commonly found in lentic and semi-lotic environments associated with macrophyte, which may result in differences in exposure to parasites. The study of parasites of small size fishes will enable the understanding of the mechanisms that affect parasite-host interaction as well as the environmental factors that drive the structuring of their parasitic communities. From these informations two studies on the parasitic fauna of the red eye tetra Moenkhausia forestii collected in semilotic environments from upper Paraná River floodplain were developed: (i) the effect of abiotic variables on the parasite community structure of a small size fish in a Neotropical floodplain, and (ii) organization of parasitic infracommunities of a small size fish from Upper Paraná River floodplain, Brazil.